Uma solução para qualidade de contexto baseada em ontologia e lógica nebulosa com aplicação em monitoramento de sinais vitais em UTI - Sena, Márcio Vinícius Oliveira (2016)
More than a decade after the first training paradigm Computer Context Sensitive, the term Quality of Context (QoC) emerged in a setting filled with services that provide userapplication interactions seamlessly, highlighting the need for managers of information context. These infrastructures that handle context information, CMS (Context Management System), are full of inputs and outputs relevant data or not. The relevance of information is studied by many lines of sensitive computing the context, including QoC. Although there are a large number of QoC metrics, the literature still lacks general values to characterize the relevance of context information, ie from metrics produce an overall value that represents the importance of information. The objective of this work is to propose, from fuzzy logic, a combination of metrics in order to produce a QoC value for each information received, and possible disposal, if this information does not meet the expected relevance, described in this work by policies of QoC. In order to disseminate the context of consumers that information produced, this research proposes also, from an ontology domain independent QoC, annotate semantically the data that refer to the quality of information, thus avoiding the need for new measures in a short-term time. Finally, this paper presents the application of the solutions found in a case study of monitoring vital signs of patients in ICU.